Variability in moral disengagement and its relation to offending in a sample of serious youthful offenders - Cardwell, Stephanie M. (Criminal justice and behavior, 2015)
Bandura?s theory of moral disengagement (MD) refers to the freeing of oneself from moral or ethical standards to engage in wrongdoing. Little is known about heterogeneity in MD among serious adolescent offenders, how MD changes over time in the transition from adolescence to early adulthood, and how such heterogeneity corresponds to offending. We used data from the Pathways to Desistance study, a longitudinal study of a sample of serious youthful offenders followed for 7 years, to examine trajectories of MD as well as the relationship of these trajectories to offending. Furthermore, we assessed whether MD varied by demographic and individual characteristics. Results indicated the presence of three trajectories: low, moderate, and high patterns. Females and Whites were more likely to be in the low-MD trajectory, whereas Hispanics were more likely to be in the high-MD trajectory. Respondents in the moderate or high-MD trajectories had more re-arrests at the 7-year follow-up relative to those in the low-MD trajectory, net of controls.